German Speaking Learning Techniques Used by German Class Xl of Language Teachers at SMA Negeri 7 Malang - Ilka Valentina Adi Aristawati; Deddy Kurniawan (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2023)
This study aims to describe the problems faced by students in learning to speak German and various German speaking teaching techniques that are carried out by German teachers at this time and during distance learning during the pandemic. This research is a type of descriptive qualitative research. The source of the data in this study was a German language teacher in class Xl of SMA Negeri 7 Malang. The data in the study were obtained from the observations of two colleagues and also interviews with the German class Xl language teacher at SMA Negeri 7 Malang. The results of the observations show that the students of class XI Language are more enthusiastic about teaching speaking German in the Face-to-face Learning system. The techniques used by the teacher in the Face-to-Face Learning system are singing techniques, techniques for explaining material on the LCD, and playing techniques. However, in the Distance Learning system, the only technique used by the teacher is to display the material on Zoom or Google Meet.